Varieties of Post-Classical and Byzantine Greek - Bentein, Klaas; Janse, Mark, 1959- (Trends in linguistics. Studies and monographs., 2020)
Linguistic varieties such as female speech, foreigner talk, and colloquial language have not gone unnoticed when it comes to Classical Greek, but little is known about later periods of the Greek language. In this collective volume leading experts in the field outline some of the most important varieties of Post-classical and Byzantine Greek, basing themselves on a broad range of literary and documentary sources, and advancing a number of innovative methodologies. Close attention is paid to the linguistic features that characterize these varieties, with in-depth discussions of lexical, morpho-syntactic, orthographic, and metrical variation, as well as the interrelationship between these different types of variation. The volume thus offers valuable insights into the nature of Post-classical and Byzantine Greek, laying the foundation for future studies of linguistic variation in these later stages of the language, while at the same time providing a point of comparison for Classical Greek scholarship.